Value-add in technical analysis on the JSE Bond Market - Haddad, Zavier (Division of Actuarial Science, 2018)
Trading on the JSE Bond Market is still done in an archaic fashion when compared to the highly digitalised trading done within the equities markets in South Africa, indicating there is less market efficiency within bond trading. Technical analysis relies on market inefficiencies to achieve an informational advantage and so there could be technical analysis based trading opportunities within bond trading. Bollinger Bands are one of the more prominent technical analysis methods. In this dissertation they are used in trading simulations to generate buy and sell signals in order to test if there is any value-add in their implementation. The dissertation attempts improve Bollinger Band based trading in two ways. The first involves attempts to more accurately estimate the underlying distribution of the time series, that is assumed to be normal in the standard methodology. It is shown that no additional benefit is derived from the alternative distribution estimation methods. Bollinger Bands make an assumption of stationarity on the time series on which they are implimented and so the second attempt at improved accuracy addresses this notion. Cointegration is used to generate linear combinations of bonds that are stationary, leading to more accurate application of the Bollinger Bands. The stationary combination of bonds produces positive results from the trading simulations, primarily within the combinations that are generated from a linear combination of less bonds and that posses larger variation. Not considering the liquidity assumtions, the positive results show that there is value-add within specific technical analysis based trading strategies.